Supersymmetric quantum cascade laser array - Jin, Yuhao (2024)
Electrically injected supersymmetric (SUSY) quantum cascade laser (QCL) array of the wavelength at around 13.4 μm has been demonstrated. By applying SUSY transformations to the main array with five laser elements, a lossy superpartner array with four laser elements is constructed. As a result, except for the fundamental supermode, which is confined in the main array, other high order supermodes penetrating into the superpartner array are suppressed. By selectively pumping the main array, the fabricated SUSY QCL array can emit light with a near-diffraction-limited (D.L.) beam over the whole dynamic range, with the full-width half-maximum up to 11.7° in the lateral direction and the output peak power up to 406 mW in pulsed operation at room temperature, which is 3.6 times the power of a single ridge laser of the same laser length. Furthermore, the far field tuning through the mode switching of fundamental and high order supermodes is realized experimentally, by electrically adjusting the gain and loss in the superpartner array, which agrees well with the designs. The electrically far field tunability has great potential to find applications in beam steering.